Blood loss in the minimally invasive posterior approach to total hip arthroplasty: a comparative study - Jose Ricardo Negreiros Vicente; Alberto Tesconi Croci; Olavo Pires de Camargo (Clinics, 2008)
AIMS: Our primary aimwas to evaluate whether there is really less bleeding in patients for whom the minimally invasive posterior approach is used in comparison with the direct lateral approachfor primary total hip arthroplasty. Our secondary aim was to evaluate the clinical functional results after six months as well as the postoperative radiographic result. METHODS: In a comparative non-random prospective study, 76 adult patients underwent elective total hip arthroplasty using one of two approaches. The minimally invasive posterior approach (34 cases; mini-incision group) was compared with the standard direct lateral approach (42 cases; control group). RESULTS: Lower total estimated bleeding (means of 1083.5 ml versus 1682.3 ml; p < 0.001) and lower intraoperative bleeding (means of 745.6 ml versus 1282.8 ml; p < 0.001) were found in the mini-incision group. There was, however, no difference in the volume of blood drained after the operation (means of 340 ml and 399 ml; p = 0.77). There was also a difference between the two groups regarding the need for allogenic transfusion (8.8% in the mini-incision group versus 28.6%, p = 0.02). We observed a better clinical result in the mini-incision group (p = 0.002) despite the lack of difference between the two groups in relation to the radiographic result. DISCUSSION: Our results draw attention to the possibility that other authors may have underestimated blood losses when using minimally invasive approaches. CONCLUSION: The minimally invasive approach gave rise to a positive final impression with regard to lower blood loss.